2017
DOI: 10.1159/000479427
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Character Coding Method Is Not Phylogenetically Neutral: A Test Case Using Hominoids

Abstract: The early stages of phylogenetic inference from morphological data involve a sequence of choices about which analytical methods to employ. At each stage, the selection of one method over another can dramatically impact tree inference. Phylogenetic hypotheses are sensitive to decisions relating to which taxa and characters to select for analysis, whether and how to delimit character states, which taxa to use as outgroups, and how to account for character dependence. Using extant hominoids as a test case, I quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Indeed, the problem of discretizing continuous traits has been the subject of a four‐decade‐long debate in phylogenetic systematics, and none of the many discretization methods available (e.g. divergence weighting, step‐matrix gap‐weighting, implied weighting – Bardin et al, 2014; Gift & Stevens, 1997; Wiens, 2001) have been shown to accurately represent the original distribution of continuous traits (Bardin et al, 2014; Raven & Maidment, 2017; Worthington, 2017). Additionally, the uneven temporal distribution of terrestrial Konservat‐Lagerstätten (Eliason et al, 2017) may differentially impact the record of amniote eggs with a thin or absent CL, and statistical approaches that consider probability of preservation could be used to put confidence bounds on estimated ancestral states (Eliason et al, 2017; Marjanović & Laurin, 2008; Marshall, 2019; Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the problem of discretizing continuous traits has been the subject of a four‐decade‐long debate in phylogenetic systematics, and none of the many discretization methods available (e.g. divergence weighting, step‐matrix gap‐weighting, implied weighting – Bardin et al, 2014; Gift & Stevens, 1997; Wiens, 2001) have been shown to accurately represent the original distribution of continuous traits (Bardin et al, 2014; Raven & Maidment, 2017; Worthington, 2017). Additionally, the uneven temporal distribution of terrestrial Konservat‐Lagerstätten (Eliason et al, 2017) may differentially impact the record of amniote eggs with a thin or absent CL, and statistical approaches that consider probability of preservation could be used to put confidence bounds on estimated ancestral states (Eliason et al, 2017; Marjanović & Laurin, 2008; Marshall, 2019; Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%